Early Deformation of Deep Brain Stimulation Electrodes Following Surgical Implantation: Intracranial, Brain, and Electrode Mechanics - Chapelle, Frédéric; Manciet, Lucie; Pereira, Bruno; Sontheimer, Anna; Coste, Jérôme; El Ouadih, Youssef; Cimpeanu, Ruxandra; Gouot, Dimitri; Lapusta, Yuri; Claise, Béatrice; Sautou, Valérie; Bouattour, Yassine; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: Although the deep brain stimulation is nowadays performed worldwide, the biomechanical aspects of the electrode implantation received little attention, mainly as the physicians focused on the medical aspects, such as the optimal indication of the surgical procedure, the positive and adverse effects and the long-term follow-up. We aimed to describe electrode deformations and brain shift immediately after implantation, as it may highlight our comprehension of intracranial and intracerebral mechanics. Mat-Methods: Sixty electrodes of thirty patients suffering of severe symptoms of Parkinson’s disease and essential tremor were studied. They consisted of 30 non-directional electrodes and 30 directional electrodes, implanted 42 times in the subthalamus and 18 times in the ventrolateral thalamus. We computed the x (transversal), y (anteroposterior), z (depth), torsion and curvature deformations, along the electrodes from the entrance point in the braincase. The electrodes were modelized from the immediate postoperative CT-Scan using automatic voxel thresholding segmentation, manual subtraction of artifacts and automatic skeletonization. The deformation parameters were computed from the curve of electrodes using a third order polynomial regression. We studied these deformations according to the type of electrodes, the clinical parameters, the surgical-related accuracy, the brain shift, the hemisphere and three tissue layers, the gyration layer, the white matter stem layer and the deep brain layer (type I error set at 5%). Results: We found that the implanted first-hemisphere coupled to the brain shift and the stiffness of the type of electrode impacted on the electrode deformations. The deformations were also different according to the tissue layers, to the electrode type and to the first-hemisphere-brain-shift effect. Conclusion: Our findings provide information on the intracranial and brain biomechanics and should help further developments on intracerebral electrode design and surgical issues.